2016
DOI: 10.1186/s12862-016-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Female cats, but not males, adjust responsiveness to arousal in the voice of kittens

Abstract: BackgroundThe infant cry is the most important communicative tool to elicit adaptive parental behaviour. Sex-specific adaptation, linked to parental investment, may have evolutionary shaped the responsiveness to changes in the voice of the infant cries. The emotional content of infant cries may trigger distinctive responsiveness either based on their general arousing properties, being part of a general affect encoding rule, or based on affective perception, linked to parental investment, differing between spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In several immunological studies in species with ARTS, the hypotheses and predictions are not clearly articulated. Males and females are dissimilar in so many ways that it is not surprising to find one more difference (e.g., Konerding et al, 2016). Differences between the 2 sexes could be predicted using relatively weak arguments, but if differences are found, there is no way of really knowing whether they indeed support a particular hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In several immunological studies in species with ARTS, the hypotheses and predictions are not clearly articulated. Males and females are dissimilar in so many ways that it is not surprising to find one more difference (e.g., Konerding et al, 2016). Differences between the 2 sexes could be predicted using relatively weak arguments, but if differences are found, there is no way of really knowing whether they indeed support a particular hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We expected a shift to a left ear preference (i.e., more left than right head turns) for high compared to low arousal calls in female cats only. As males showed no behavioral differences between either arousal categories ( Konerding et al, 2016 ) we expect them to show the typical right ear/left hemispheric dominance to both types of this species-specific vocalization.…”
Section: Introductionmentioning
confidence: 89%
“…In our previous publications, we already showed that kitten isolation calls show changes in acoustic properties during low versus high arousal behavioural conditions ( Scheumann et al, 2012 ) and that these differences in conveyed arousal induced concordant differences in responsiveness in female cats ( Konerding et al, 2016 ). Thereby, females oriented significantly faster towards the sound-source to high versus low arousal kitten calls.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations